Comparative outcomes of exposing human liver and kidney cell lines to tungstate and molybdate. (22nd November 2021) - Sachdeva, Sherry; Maret, Wolfgang
Abstract: Tungsten has no known function in humans and is a relatively new contaminant, whereas molybdenum, its congener in the periodic table, is a nutritionally essential element. In addition to early studies on molybdosis in ruminants, their toxic effects in the form of tungstate and molybdate have been addressed primarily in rodents and are predominantly mediated by inducing oxidative stress in various tissues. The purpose of this study was to evaluate the differences between tungstate and molybdate in human liver (HepG2) and kidney (HEK293) cell lines in terms of retention in cells, effect on reactive oxygen species, and activities of xanthine oxidase and phosphatases. The cell lines were exposed to tungstate or molybdate (1 µM to 10 mM) for 24 h, lysed and analyzed for the above biochemical parameters. Despite the chemical similarity of the two anions, cell-specific differential effects were observed. At all concentrations, tungstate was retained more in HEK293 cells while molybdate was retained more in HepG2 cells. HepG2 cells were more sensitive to tungstate than molybdate, showing reduced viability at concentrations as low as 10 µM. Exposure to either anion resulted in the inhibition of protein tyrosine phosphatases at 1 mM and an increased production of reactive oxygen species (ROS) at 100 µM despite their inhibition of the ROS-producing molybdenum enzyme xanthine oxidase. In conclusion, the results indicate that excess of nutritionally essential molybdate or non-essential tungstate causes toxicity by affecting ROS- and phosphorylation-dependent signaling pathways and ensuing gene expression.